TRADISI SULUK (Studi pada Jama’ah Tarekat Naqsyabandiyah di Desa Gunung Sahilan, Kecamatan Gunung Sahilan, Kabupaten Kampar) - Vinola Syawli Zahra; Jonyanis " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Islamic religion itself in the Qur'an has equipped, demonstrated, and taught humans about ways to achieve peace of life. One concept that is in the Qur'an is by way of remembrance. The Naqshbandiyah Order has one of the methods of dhikr or a way to draw closer to Allah by performing suluk. The focus of this research is "The Tradition of Suluk (Study of the Naqsyabandiyah Congregation in Gunung Sahilan Village, Gunung Sahilan District, Kampar Regency”.. The purpose of this research is to find out the background of the naqsyabandiyah congregation persisting with the suluk tradition as well as knowing the activities of the suluk congregation and to find out the meaning of suluk for the congregation of the naqsyabandiyah congregation. The research method used is a qualitative research method. Research location in Gunung Sahilan Village. In determining the research subject using purposive sampling technique that is predetermined based on criteria. The number of informants in this study amounted to 8 people. The theory used is the Theory of Structural Functionalism from Talcott Parson. Data collection techniques used were observation, interviews and documentation. The result of this general research is that the congregation of the naqsyabandiyah congregation survives with the suluk tradition because there are perceived benefits as well as the pilgrims feel the difference in the implementation of worship when attending suluk with worship at home where when performing worship at home, worship devotion they feel not as big as when suluk and suluk have meaning as a reminder of death so that each congregation remembers Allah by following suluk. Keywords: Suluk, Naqsyabandiyah Tariqa.